MEMS-Based Planar Incandescent Microfilaments With Low Voltage Operation - Jyun-Hao Liao; Chien-Ju Chen; Chia-Jui Yu; Meng-Chyi Wu (IEEE Journal of the Electron Devices Society, 2020)
In this article, we report the design and fabrication for planar-type incandescent microfilaments on the silicon on insulator (SOI) wafer. The micro-electro-mechanical systems (MEMS) process with XeF2 etching is used to construct the suspension structure for the reduction of thermal conduction. The fabricated line-type microfilament has a low operation voltage of 4 V. Besides, the operation voltages for the 1 × 4, 5×5, 6×6, and 7×7 arrays at 50 mtorr are 4.0, 9.0, 9.5, and 9.5 V, respectively. The 1×4 array filament exhibits the measured lifetime of 200 hrs and the predicted lifetime of about 570 hrs. The microfilament has a continuous broadband spectrum that covers from visible light extended to over 3 μm, which is a suitable light source for near-infrared spectroscopy.